MASCULINE LANGUAGE IN INDONESIAN NOVELS: A FEMINIST STYLISTIC APPROACH ON BELENGGU AND PENGAKUAN PARIYEM - Supriyadi . (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2014)
Belenggu is a novel written by Armijn Pane in 1938, whereas Pengakuan Pariyem is a lyrical novel written by Linus Suryadi AG that published in 1980. Both are interested to be analyzed from linguistic aspects, especially in relation to gender dan patriarchal issues. In this case, the proper approach is feminist stylistics by Sara Mills since it analyzed literary works from linguistic aspects and then is enlarged on the contexts of surroundings when it was published. The results are that Belenggu basically used masculine languages including word, phrases, clauses, sentences, and discourses when it is related to its contexts. Contextually, Belenggu represented author responses to conditions of his society in which women tried to insist their rights for equality (to men). It also represented author’s critic to women since it is better that women still work domestically and support her husband. Meanwhile, Pengakuan Pariyem is a lyrical novel that considers men and women have mutual relationships although women still work domestically and men work outside.